Review on anti-epileptic and anxiolytic plants used in Manasamitra Vatakam: an ayurvedic herbomineral formulation - V. SRIKALYANI; K. ILANGO (International Journal of Pharma and Bio Sciences, 2019)
Ayurveda is an ancient system of Indian traditional medicine which has been facing a numerous challenges and has undergone various obstacles in the global market. Ayurvedic herbal formulations has been widely used for the treatment of various neurological disorders like epileptic seizures, insomnia, manic illness, brain stroke, depression and for anxiety disorders which are highly comorbid psychiatric conditions where the occurrence of all these neurological disorders often leads to cardiac failure. The risk of death rate has been risen four times the current population and the greatest risk in the mortality is seen in elderly individuals. Manasamitra Vatakam is one of the traditional ayurvedic herbomineral formulation (AHMF) texted in Sahasrayogam, it is a composite mixture of 55 plant extracts used in the treatment of various neurological disorders. The main aim of the present review is to focus on the recurrently used medicinal plants effectiveness for the treatment of anti-convulsions and anxiolytic disorders, the pharmacological activity and the bioactive markers responsible for the therapeutic efficacy.